Ulstermen and Identity in the Chinese Maritime Customs Service, 1859-1949 - Morrison, Clare Marie (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2024)
This research will assess the cultural identity of Ulstermen working in the Chinese Maritime Customs Service, 1859-1949. Sir Robert Hart joined the Customs Service in 1859, and by 1863 was the head of the organisation. The Customs was a unique, international cultural environment, where most senior employees were foreign. As Inspector General, Hart became personally involved in the hiring process. As a result, a significant number of Irishmen, especially Ulstermen, were hired. These included Stanley Fowler Wright, a Queen's University Belfast alumnus, and Sir Frederick Maze, Hart's nephew, who eventually became Inspector General himself. Hart refers to himself in his extensive diaries and correspondence as Irish, British, an Ulsterman, and, occasionally, English. For Hart, these identities were not contradictory, rather he had an understanding of both his own complicated Ulster heritage and the how his Western cultural identifiers were perceived by other foreign staff and by Chinese officials. This research will explore the ways in which Ulstermen referred to themselves and understood their identity in context of both the changing political environment in China, and the redrawing of state boundaries in the U.K. and Ireland. It will assess the legacy and impact of Hart's hiring practices, and evaluate how these men managed their multiplicitous identities, while working in an environment that was so far removed from the country and politics that created them. This thesis will also be to contribute to the wider literature about Irish identities after partition. While there has been significant discussion of identities in the Free State and, later, the Republic of Ireland, there is a gap regarding how new Northern Irish identities responded to the changing landscape. Evaluating how men from this environment responded, while being so far removed from it, will offer a new insight into the evolution of identities on the island.
APPROVED